Friction and wear of Stellite 6B during sliding against rubber compound with varied carbon fiber content. (February 2022) - Han, Deshang; Pan, Yi; Li, Shaoming; Xu, Minghui; Xiao, Xinxin; Hao, xiaoyong; Huang, Enqun; Wang, Chuansheng; Bian, Huiguang
Abstract: As an essential rubber mixing equipment in continuous production, an internal mixer should have a long service life while operating at high intensity. Studies show that at these severe operating conditions, end face wear of the internal mixer is inevitable. It is worth noting that the end face is an important part of the closed mixing chamber. The head of the rotor shaft is inserted into the copper ring of the sealing plate, the sealing plate and the mixing chamber are pressed together by bolts. There is a gap between the rotors and the mixing chamber. During the mixing process, the mixed rubber in the mixing chamber is in direct contact with the end face, the end face metal is frictional and abraded. Wear of the end face may result in a gap between the mixing chamber and the end face, leading to material leakage. As the leakage intensifies, the gap between the end face and the mixing chamber further increases, thereby forming negative feedback. This phenomenon not only affects the chemical composition of the rubber but also reduces the mixing efficiency and decreases the performance of the rubber compound. The end surface material is cobalt chromium molybdenum tungsten alloy. The alloy model is Stellite 6B. In the present study, the influence of different amounts of CF on the friction and wear of the end face is analyzed from the chemical composition perspective. Moreover, the ratio of corrosion wear to abrasive wear is calculated. The obtained results show that as the amount of CF in the compound increases, the proportion of the corrosive wear of the compound to the metal increases, while the proportion of abrasive wear decreases. The highest proportion of corrosive wear and the lowest amount of metal wear can be achieved for the CF amount of 9 phr. As the CF content in the composition increases, the ratio of the corrosive wear of the rubber compound to metal decreases, while the proportion of abrasive wear and the total amount of wear to metal increases. Highlights: Studies show that at these severe operating conditions, end seal wear of the internal mixer is inevitable. This study analyzed the effect of different additions of CF on the friction and wear of the end seal. The highest proportion of corrosive wear and the lowest amount of metal wear can be achieved for the CF amount of 9 phr.